Effectiveness of Sacubitril/Valsartan in Heart Failure with Reduced Ejection Fraction Using Real-World Data: An Updated Systematic Review and Meta-Analysis - Alaa Rahhal (14150403) (2022)
We conducted a systematic review and meta-analysis to assess all-cause mortality and heart failure (HF) hospitalization with sacubitril/valsartan (S/V) compared to standard HF therapy in patients with HF with reduced ejection fraction (HFrEF) using real-world data. We performed a systematic review and meta-analysis following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We searched PubMed and Google Scholar for the observational studies published in English exploring the clinical outcomes of S/V use in HFrEF till March 14, 2022. Two independent reviewers assessed the quality and risk of bias of the included studies. A random-effect model was used to combine data. The outcomes assessed were all-cause mortality and HF hospitalization associated with S/V use in comparison to standard HF therapy. A total of 9 observational studies comparing S/V to Angiotensin-converting enzyme inhibitors (ACE-I)/Angiotensin II receptor blockers (ARB) in HFrEF were included in the systematic review, with more than 32000 patients included in the final analysis. Overall, S/V use was associated with a significant reduction in all-cause mortality (Risk Ratio [RR] = 0.70, 95% CI 0.53-0.93, I2 = 83%) and HF hospitalization (RR = 0.62; 95% CI, 0.48-0.80, I2= 94%). Similar to the landmark controlled evidence, real-world data of S/V use in HFrEF demonstrated a significant reduction in all-cause mortality and HF hospitalization. Other Information Published in: Current Problems in Cardiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cpcardiol.2022.101412